Комиссия Эмигрантологии Славян и Международный Конгресс Славистов в Белграде - Suchanek, Lucjan (Acta Polono-Ruthenica, 2019)
From 20 to 27 August 2018, the International Slavic Congress took place in Belgrade. The pro-gram of the Commission held meetings that are accredited (affiliated) at the International Committee of Slavists. The congress of researches on emigration provided an opportunity to discuss the current state of research and their prospects for further development. The author of the article discusses the specifics of emigration research, paying particular attention to the achievements of Polish stud-ies, and points out the most important tasks facing the Board and the Bureau of the Commission. An important stage in the activities of the commission is the decision to move its headquarters to Olsztyn, which strengthens the Institute of Eastern Slavic studies as one of the Leading centers of emigration research, not only in Poland, but also in European science.